A taxonomic survey of marine brachyuran crabs in Lapinig Bay, Northern Samar. - Robles, Lady Angela M.; Varona, Gracia F. (Lady Angela M. Robles, 2018)
The Samar islands have no inventory on brachyuran crab species. Moreover, no studies related to taxonomy of all brachyuran crabs have been conducted in Lapinig Bay, Northern Samar. Thus, this study is aimed to survey the marine brachyuran crabs present in the municipality. Brachyuran crabs were collected in accessible collecting stations within selected areas of the bay through the differences in water depth from January to March 2018.
A total of 128 individual brachyuran crabs belonging to 20 species from nine families were collected and identified in Lapinig Bay, Northern Samar. Uca tetragonon (Ocypodidae) was the prominent of all brachyuran crab species, making up 18.75% of all individual crabs. It was followed by Uca neocultrimana (Ocypodidae) and Varuna litterata (Grapsidae). All the other species had lower abundances. The crab species were found in a variety of habitats from intertidal to subtidal zones with sandy to muddy substratum. Difference in crab composition and abundance was attributed to the depth where it was collected.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.